Model Pemasaran Produk Industri Kreatif Rumah Tangga di Kawasan Wisata Karst Rammang-Rammang Kabupaten Maros - Anggun Sari Sasmita (Media Wisata, 2019)
Creative industry has the potential to develop in the Karst Tourism Area of Ramming-Ramang Regency, Maros Regency as an effect of the increase of the tourist visits in this area. This study aims to help find a model of creative industries marketing in the Rammang-Ramamng Karts Tourism Area, Maros Regency. This research use descriptive qualitative approach. Research data obtained through interviews and questionnaires. Data analysis was performed using the SWOT Analysis technique. Stages of research activities include the initial observation stage, data collection stage, preparing the marketing model stage, and marketing model socialization stage. The results of the study showed community around the tourism area need training and assistance in managing the creative industries using the 4P concept (product, place, price and promotion